The Gut Microbiota Regulates Endocrine Vitamin D Metabolism through Fibroblast Growth Factor 23 - Bora, Stephanie A.; Kennett, Mary J.; Smith, Philip B.; Patterson, Andrew D.; Cantorna, Margherita T. (Frontiers in Immunology, 2018)
To determine the effect of the microbiota on vitamin D metabolism, serum 25hydroxyvitamin D(25D), 24,25dihydroxyvitamin D (24,25D) and 1,25dihydroxyvitamin D (1,25D) were measured in germfree (GF) mice before and after conventionalization (CN). GF mice had low levels of 25D, 24,25D and 1,25D and were hypocalcemic. CN of the GF mice with microbiota, for 2wks recovered 25D, 24,25D and 1,25D levels. Females had more 25D and 24,25D than males both as GF mice and after CN. Introducing a limited number of commensals (8 commensals) increased 25D and 24,25D to the same extent as CN. Monocolonization with the enteric pathogen Citrobacter rodentium increased 25D and 24,25D, but the values only increased after 4 wks of C. rodentium colonization when inflammation resolved. Fibroblast growth factor (FGF)23 was extremely high in GF mice. CN resulted in an increase in TNF-± expression in the colon 2d after CN that coincided with a reduction in FGF23 by 3d that eventually normalized 25D, 24,25D, 1,25D at 1wk post-CN and reinstated calcium homeostasis. Neutralization of FGF23 in GF mice raised 1,25D, without CN, demonstrating that the high FGF23 levels were responsible for the low calcium and 1,25D in GF mice. The microbiota induce inflammation in the GF mice that inhibits FGF23 to eventually reinstate homeostasis that includes increased 25D, 24,25D and 1,25D levels. The microbiota through FGF23 regulates vitamin D metabolism.